A combined spectroscopic investigation of cobalt oxide films prepared by DC reactive sputtering - Azevedo Neto, Nilton Francelosi [UNESP] (2023)
The structure and vibrational characteristics of cobalt monoxide and tetraoxide films, prepared by direct-current DC reactive sputtering, were investigated by different characterization techniques. According to X-ray diffraction analyses, the development of the Co3O4 phase takes place under low discharge power and high substrate temperature (80 W-623 K) conditions, whereas the CoO phase predominates when adopting high discharge power and low substrate temperature (240 W-473 K). Results of infrared absorption and Raman scattering spectroscopies indicate the presence of Co3O4 in all films, that are compatible with the optical transmittance spectra in the UV-Vis-NIR range − showing electronic transitions due to Co2+/3+ cations (related to the Co3O4 spinel structure) in the films deposited at 80 W-623 K and, to a lesser extent, at 240 W-473 K conditions. The investigations include Raman scattering measurements in the 83–623 K range. The results evidence a mixture of phases in the 240 W-473 K film, whose main Raman scattering peaks evolve irreversibly towards Co3O4 upon increasing measurement temperatures. Altogether, the present report provides deeper information about the cobalt oxide phases that shall be useful to improve the control of properties and production of cobalt oxide films by DC reactive sputtering.